Paediatric Crohn disease patients with stricturing behaviour exhibit ileal granulocyte–macrophage colony‐stimulating factor (GM‐CSF) autoantibody production and reduced neutrophil bacterial killing and GM‐CSF bioactivity. (18th April 2013) - Jurickova, I.; Collins, M. H.; Chalk, C.; Seese, A.; Bezold, R.; Lake, K.; von, D.; Frischer, J. S.; Falcone, R. A.; Trapnell, B. C.; Denson, L. A.
Summary Granulocyte–macrophage colony‐stimulating factor (GM‐CSF) autoantibodies are associated with stricturing behaviour in Crohn disease (CD). We hypothesized that CD ileal lamina propria mononuclear cells (LPMC) would produce GM‐CSF autoantibodies and peripheral blood (PB) samples would contain GM‐CSF neutralizing capacity (NC). Paediatric CD and control PBMC and ileal biopsies or LPMC were isolated and cultured and GM‐CSF, immunoglobulin (Ig)G and GM‐CSF autoantibodies production were measured by enzyme‐linked immunosorbent assay (ELISA). Basal and GM‐CSF‐primed neutrophil bacterial killing and signal transducer and activator of transcription 5 (STAT5) tyrosine phosphorylation (pSTAT5) were measured by flow cytometry. GM‐CSF autoantibodies were enriched within total IgG for LPMC isolated from CD ileal strictures and proximal margins compared to control ileum. Neutrophil bacterial killing was reduced in CD patients compared to controls. Within CD, neutrophil GM‐CSF‐dependent STAT5 activation and bacterial killing were reduced as GM‐CSF autoantibodies increased. GM‐CSF stimulation of pSTAT5 did not vary between controls and CD patients in washed PB granulocytes in which serum was removed. However, GM‐CSF stimulation of pSTAT5 was reduced in whole PB samples from CD patients. These data were used to calculate the GM‐CSF NC. CD patients with GM‐CSF NC greater than 25% exhibited a fourfold higher rate of stricturing behaviour and surgery. The likelihood ratio (95% confidence interval) for stricturing behaviour for patients with elevation in both GM‐CSF autoantibodies and GM‐CSF NC was equal to 5 (2, 11). GM‐CSF autoantibodies are produced by LPMC isolated from CD ileal resection specimens and are associated with reduced neutrophil bacterial killing. CD peripheral blood contains GM‐CSF NC, which is associated with increased rates of stricturing behaviour.